Biorrefinarias: a utilização de lodo de esgoto para a produção de ácidos graxos voláteis, polihidroxialcanoatos e biocrude - Di Favari, Isabella Durante (Universidade Federal de São Carlos, 2023)
This work aims, firstly, to present a bibliographic review on circular bioeconomy and biorefineries. The circular economy seeks to be an alternative to the linear economy, its objective is to minimize single-use products, reaffirming concepts such as recycling, transforming waste into products and minimizing or completely eliminating waste. The circular bioeconomy aims to use raw materials from renewable and sustainable sources. The concept of biorefinery was proposed based on the problem of the current dependence on oil derivatives and fossil fuels and their political and environmental consequences. In biorefineries, using biomass that would otherwise be discarded, it is possible to produce energy and other products. In this way, waste is used to obtain value-added and, above all, sustainable products. For a more detailed review, sewage sludge was chosen as the raw material to be further investigated, due to its wide availability in the country and low economic value. With regard to products, the focus is on short-chain volatile fatty acids (VFAs), such as acetic acid and lactic acid, from sludge fermentation, as they are extremely necessary and used in various types of industries, polyhydroxyalkanoates (PHAs), substances similar to polyester that are the result of the metabolism of some bacteria in substrates rich in fatty acids, can be applied in several areas in the substitution of polymers of fossil origin and, finally, biocrude, an oil obtained from the hydrothermal liquefaction of treated sludge and which has the possibility of being used in refineries to supplement or replace fossil oil. The products chosen for an in-depth study have economic, technological and sustainable advantages. A broad view of the situation of sewage sludge in Brazil is also carried out, in order to reflect on the possibility of implementing sludge biorefineries that produce AGVs, PHAs and biocrude in Brazil.
Biorefineries: the use of sewage sludge for the volatile fatty acids, polyhydroxyalkanoates and biocrude production
Keywords: Biorrefinarias; Bioeconomia circular; Biomassa; Biorefineries; Circular bioeconomy; Biomass; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA SANITARIA